The Dynamics of Blood Drop Release from Swinging Objects in the Creation of Cast‐off Bloodstain Patterns1. Issue 2 (5th July 2018) - Williams, Elisabeth M. P.; Graham, Emma S.; Jermy, Mark C.; Kieser, David C.; Taylor, Michael C.
Abstract: Although the characteristics of cast‐off bloodstain patterns are well known, the physics of the mechanism by which they are created is poorly understood. The aim of this work was to describe the process by which blood droplets disengage from swinging objects. Cast‐off droplets were recorded using high‐speed digital video photography, and the resulting cast‐off patterns were analyzed to draw inferences about the trajectories of individual drops. Blood on the object's distal end formed ligaments, which subsequently disintegrated into droplets. Initial droplet trajectories were approximately tangential to the trajectory of the location on the object from which the droplet was released. The application of the laws of physics to the mechanism of cast‐off is discussed, and the process of drop formation is compared to that of passive drop formation. A technical description of cast‐off is proposed, and a diagram to aid investigators in interpreting cast‐off patterns at crime scenes is offered.